Strategi Pengembangan Usaha pada PITS-Stop Kopi - Lailatul Farichah; Rahmad Jumadi; Raden Achmad Djazuli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the internal and external factors that influence the development of the Pit-Stop Coffee business and formulate an appropriate business development strategy. Pit-Stop Kopi is one of the big coffee brands in Gresik City which has been operating since 2017 and has three branches. This research technique uses SWOT analysis. The research results show that there are 4 strength factors and 4 weakness factors in the internal factors owned by Pit-Stop Coffee, and there are 4 opportunities and 3 threats contained in the external factors owned by Pit-Stop Coffee. The right strategy for developing this business is to use an aggressive strategy, with several alternatives, namely maintaining product quality, maximizing sales through online food ordering applications, and creating social events to attract new customers. It is hoped that this strategy can increase the competitiveness and sustainability of the Pit-Stop Coffee business in the face of intense competition.